Domain Vagueness and the Epistemic Background - Şener, Nilüfer (Chicago Linguistic Society Publications, 2007)
This paper shows that evidentials provide convenient environments for the manifestation of the domain vagueness requirement on Free Choice items such as herhangi bir in Turkish. In English, certain modals restrict the use of Free Choice any. Dayal (1998) suggests that this restriction is due to the domain vagueness requirement on this item. I demonstrate that in Turkish, speakers epistemic background regulates the legitimacy of Free Choice herhangi bir implying that vagueness is a basic property of this item. I propose that the interesting interaction of evidentials with Free Choice item herhangi bir can be accounted for by assuming Kratzer's (1987) theory of modal interpretation, Izvorski's (1997) account for evidentials and Dayal's (1998) proposal on Free Choice any.
Keywords: epistemic modality; domain vagueness; evidentiality; Free Choice items; Turkish; domain vagueness; evidentials